What happened in the mid-1990s? The coupled ocean-atmosphere processes behind climate-induced ecosystem changes in the Northeast Atlantic and the Mediterranean. (January 2019) - Alheit, Jürgen; Gröger, Joachim; Licandro, Priscilla; McQuinn, Ian H.; Pohlmann, Thomas; Tsikliras, Athanassios C.
Abstract: Northeast Atlantic marine ecosystems such as the Bay of Biscay, Celtic Sea, English Channel, Subpolar Gyre region, Icelandic waters and North Sea as well as the Mediterranean Sea show concomitant 'regime shift'-like changes around the mid-1990s, which involved all biota of the pelagial: phytoplankton, zooplankton, pelagic fish assemblages, demersal fish assemblages and top predators. These shifts were caused by complex ocean-atmosphere interactions initiating large-scale changes in the strength and direction of the current systems, that move water masses around the North Atlantic, and involved the North Atlantic Oscillation (NAO), the Atlantic Meridional Overturning Circulation (AMOC), and the subpolar gyre (SPG). The contractions and expansions of the SPG and fluctuations of the Atlantic Multidecadal Oscillation (AMO) play a key role in these complex processes. Small pelagic fish population trends were the sentinels of these changes in the mid-1990s in the ecosystems under investigation.